Skill shortages and skill mismatch in Europe: A review of the literature - Giorgio Brunello; Patricia Wruuck; Laurent Maurin (European Investment Bank (EIB), 2019)
This paper reviews the recent economic literature on skill mismatch and skill shortages with a focus on Europe. The review starts with a conceptual overview of skill mismatch and skill shortages and how to measure them. An issue discussed in the first section is the measurement of job requirements, i.e. a demand side variable, that some authors compute using surveys of individuals, which typically collect information on the supply side (educational attainment, foundation skills). Individuals, however, do not often have a reliable view of job requirements, and may actually have an incentive to inflate them. Another issue is whether skill shortages stated by employers reflect the lack of suitable candidates among job seekers or are due instead to the wage and working conditions being offered. The second section looks at how skill shortages and mismatch are affected by cyclical and structural factors. Whether mismatch is pro or counter-cyclical depends on the relative strength of cleansing effects (poor matches are destroyed in a recession) and sullying effects (in a recession skilled workers are willing to accept unskilled jobs as jobs are scarce). Structural factors contributing to skill mismatch and shortages in Europe include "megatrends", notably globalisation, digitalisation and ageing. In addition, institutional factors shaping labour markets, skill utilization and formation at national and European level can work to reinforce or mitigate skill shortages and mismatches and are an important factor mediating the impact of structural trends. The third section discusses the economic costs of skill mismatch and shortages. Mismatch not only affects individuals but can also reduce average productivity by leading to an inefficient allocation of resources across firms. The final section considers policy implications, including how responsibilities for skill development can best be shared and what role EU policies can play to better address skill shortages and mismatches.
Keywords: 330